THE APPLICATION OF CONTRUCTIVISM LEARNING MODELS IN THE PANDEMIC PERIOD TO IMPROVE STUDENTS ENGLISH FOR BIOLOGICAL LEARNING CREATIVITY IN SMA NEGERI 5 PADANGSIDIMPUAN - Batubara, Melvariani Syari (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The purpose of this study was to determine the increase in student learning creativity through the application of the constructivism learning model on English for Biology material on learning outcomes in class X MIPA-5 SMA Negeri 5 Padangsidimpuan. The method used in this research is included in Classroom Action Research. Research. The research process was carried out in 2 cycles, each of which consisted of seven stages: (1) Analysis, (2) Fact Finding, (3) Conceptualization, (4) Planning, (5) Implementation, (6) Additional Fact Finding, and (7) Evaluation. The results of this study indicate that there is an increase in students' English for Biology learning creativity by 20% through the constructivism learning model on the material of English for Biology at the Padangsidimpuan High School at SMA Negeri 5 Padangsidimpuan with a percentage of completeness reaching 50% in cycle I and 70% in cycle II, with a KKM value. 80.